Etiology and Control of Phytophthora Infestans (Mont.) De Bary in Malaysia - Mohd Yunus, Ahmad Kamil (1994)
Phytophthora infestans (Mont.) De Bary is the causal agent of late blight disease of tomato, a major destructive disease of tomato in Cameron Highlands. The study undertaken was to isolate the pathogen on artificial media. The morphology and cultural characteristics were described. Disease development of P. infestans isolates on tomato was also studied. In-vivo sensitivity of the isolates towards metalaxyl was tested. Disease epidemiology studies were conducted during the two tomato planting periods in Cameron Highlands. Three isolates of P. infestans from Cameron High lands were isolated on Rye Grain Agar (RGrA), V-8 Juice Agar (V8JA) and Rye wholemeal Agar (RWMA) allamended with antibiotics with percentage recovery of 2%, 0.1% and 0.4% respectively. The P. infestans isolates were designated as PIB/01, PIH/01 and PIKR/01. No growth was observed on the two other media viz. Pea Agar and Difco LBA. Successful isolation were aided by baiting using potato tuber slices. Morphological studies of the P. infestans isolate showed that the mean zoosporangia size was 37.25um x 19.71um, mean L/B ratio of 1.91 and mean short pedicel length of 1.60um. Mean zoospores diameter measured 9.99 um. No chlamydospores was produced in culture.